Evaluating Industrial Relations Through Dunlop’s Framework:‎Employees’ Perceptions and Organizational Effectiveness in The ‎Pharmaceutical Industry of North Coastal India - Sunand , Potula Laxmana; Sirisetti, Suresh (International Journal of Basic and Applied Sciences, 2025)
The role of industrial relations in shaping organizational effectiveness is particularly crucial in highly regulated industries such as the phar-‎maceutical sector. This study applies Dunlop’s Industrial Relations System framework to evaluate employees’ perceptions of industrial rela-‎tions and their impact on organizational effectiveness in the north coastal region of Andhra Pradesh. Utilizing a mixed-methods approach, ‎both qualitative and quantitative data were collected from employees, human resource managers, and union representatives to ensure a com-‎prehensive understanding of industrial relations dynamics. The findings highlight that effective industrial relations contribute significantly to ‎job satisfaction (78.5%), employee retention (85.2%), and productivity improvement (12.8%). Compliance with labor laws (90.5%) and ‎grievance redressal effectiveness (81.4%) were found to be the strongest predictors of overall organizational effectiveness, which was rated ‎at 84.3%. Statistical analysis using SPSS further confirmed that compliance with labor laws (R-squared: 23.2%) and employee satisfaction ‎‎(R-squared: 19.8%) had the highest positive correlations with organizational effectiveness. Conversely, labor disputes (7.3%) had a negative ‎correlation (-0.58), emphasizing the adverse effects of unresolved conflicts on workforce stability. A comparative analysis across pharma-‎ceutical companies in Visakhapatnam, Vijayanagaram, Srikakulam, and Anakapalli revealed regional disparities in industrial relations and ‎organizational performance. Visakhapatnam exhibited the highest compliance with labour laws (91.2%) and employee satisfaction (80.2%), ‎while Srikakulam faced greater challenges with higher labour dispute frequency (9.1%) and lower employee retention (79.2%). Despite ‎strong quantitative indicators, qualitative analysis revealed significant gaps in employee perceptions, particularly regarding contract-based ‎hiring, favouritism in labour policies, and delayed grievance resolution. These discrepancies highlight the need for enhanced transparency, ‎fair policy implementation, and improved training programs to bridge the gap between formal IR policies and employee experiences. This ‎study provides actionable recommendations for policymakers and industry leaders to strengthen industrial relations and enhance organiza-‎tional effectiveness in the pharmaceutical sector‎.